Use of Interactive Radio Instructional Broadcast for Primary School Pupils in Lagos State - Felicia, Dipo Adedoyin Olubunmi (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2025)
This study examines the use of Interactive Radio Instruction Broadcast (IRIB) as a tool for enhancing primary education in Lagos State, Nigeria. Amid challenges such as overcrowded classrooms, inadequate teaching personnel, and disruptions to traditional learning systems, especially during crises like the Covid-19 pandemic, radio has re-emerged as a viable medium for delivering education to hard-to-reach and underserved populations. This research investigates the accessibility, content quality, learner engagement, and educational outcomes associated with IRI among primary school pupils in Lagos State. The paper is a conceptual paper that utilises secondary data from the existing literature like scholarly books, journal articles, internet materials and media publications. The paper employs the Pedagogical Content Knowledge (PCK). This theory is relevant to this study as it charts a framework to understand how teachers can effectively integrate subject knowledge with appropriate instructional strategies when using Interactive Radio Instruction (IRI) for primary school pupils in Lagos State. The paper argued that while IRI holds significant promise in promoting foundational literacy and numeracy skills, its impact is moderated by factors such as fund, parental support, broadcast duration, electricity supply and poor signals. The paper concludes that the use of Interactive Radio Instructional Broadcast (IRIB) has proven to be a valuable educational tool for reaching primary school pupils in Lagos State, particularly in contexts where access to conventional classroom learning is limited. This paper underscores the potential of radio as a cost-effective, scalable, and inclusive medium for delivering foundational education, especially in underserved and low-resource communities.